Informational foundations for the morphometric study of placentas in twin pregnancies - Rafael Gutiérrez-Núñez (Centro Editorial Ciencias Médicas: CPICM Guantánamo, 2021)
Introduction: in Cuba there are very few morphofunctional studies of placentas from twin pregnancies that allow establishing a general morphometric pattern. Implementing these informational databases would help to improve the actions of the National Sexual and Reproductive Health Program in the country.